2022
DOI: 10.1038/s41598-022-08493-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of the right prefrontal cortex in the retrieval of weak representations

Abstract: Although recent studies have shown the importance of control in creative problem solving, the neural mechanisms of control processes engaged in retrieval of weak representations, which is closely linked to creative problem solving, remain unclear. The current study aimed to examine the neural mechanisms associated with retrieval of weak representations using functional magnetic resonance imaging and their potential relationships with creativity task performance. For this purpose, participants performed an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Digital and physical prototyping tools and open and constrained processes influence brain activity. We found that physical prototyping led to increased brain activation in channels in the right PFC, which is consistent with prior research on creative thinking and divergent cognitive processes (Yi et al, 2022). This may suggest a potential link between the tangible, hands-on nature of physical prototyping and increased creative cognitive processes.…”
Section: Further Worksupporting
confidence: 90%
“…Digital and physical prototyping tools and open and constrained processes influence brain activity. We found that physical prototyping led to increased brain activation in channels in the right PFC, which is consistent with prior research on creative thinking and divergent cognitive processes (Yi et al, 2022). This may suggest a potential link between the tangible, hands-on nature of physical prototyping and increased creative cognitive processes.…”
Section: Further Worksupporting
confidence: 90%
“…Considering the recent increase in studies identifying new functions associated with the right frontal lobe [37], which include calculation, the signi cance of awake surgery for tumors in this region is even greater. Our two cases may show a need for mapping calculation tasks during awake surgery in the right frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prefrontal dysfunction is Rating Scale; HAMA, Hamilton Anxiety Rating Scale; HAMD×HAMA, interaction between HAMD and HAMA a well-known characteristic of depression and suicidal tendencies [23]. The FP2 electrode placement refers to the right prefrontal cortex, a brain region involved in executive functions such as decision-making, working memory, and attention [24]. Structural changes in the prefrontal cortex have been associated with various psychiatric disorders, including depression and anxiety [25].…”
Section: Discussionmentioning
confidence: 99%